Thermionic emission of LaB₆–ZrB₂ quasi-binary eutectic alloy with different ZrB₂ fibers orientation - Taran, A.; Voronovich, D.; Oranskaya, D.; Filipov, V.; Podshyvalova, O. (Functional Materials, 2013)
Comparative thermionic properties investigations of the quasi-binary eutectic alloy LaB₆–ZrB₂ having both zirconium diboride fibers orientations (perpendicular and parallel) relative to the emitting surface were conducted for the first time. Thermionic current density time dependences for cross and longitudinal sections suggest that the eutectic composite material LaB₆–ZrB₂ can be used as an effective thermionic emitter also with the fibers orientation parallel to the emitting surface.